2020
DOI: 10.1101/2020.06.17.157982
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep mutational scanning of SARS-CoV-2 receptor binding domain reveals constraints on folding and ACE2 binding

Abstract: The receptor binding domain (RBD) of the SARS-CoV-2 spike glycoprotein mediates viral attachment to ACE2 receptor, and is a major determinant of host range and a dominant target of neutralizing antibodies. Here we experimentally measure how all amino-acid mutations to the RBD affect expression of folded protein and its affinity for ACE2. Most mutations are deleterious for RBD expression and ACE2 binding, and we identify constrained regions on the RBD's surface that may be desirable targets for vaccines and ant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

84
1,194
5
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 615 publications
(1,286 citation statements)
references
References 159 publications
84
1,194
5
3
Order By: Relevance
“…To map antibody-escape mutations in a high-throughput manner, we leveraged a system for expressing conformationally-intact RBD on the surface of yeast cells ( Figure 1A). As described previously (Starr et al, 2020) , we created duplicate mutant libraries of the RBD from the Wuhan-Hu-1 strain of SARS-CoV-2 that together contained nearly all possible amino-acid mutations in the 201-residue RBD (they contain 3,804 of the 3,819 possible mutations, with >95% present as single mutants). Each yeast cell carries a short 16-nucleotide barcode that identifies the RBD mutant it expresses, enabling us to rapidly characterize the composition of the RBD mutant libraries via deep sequencing of the DNA barcodes.…”
Section: A Yeast-display System To Completely Map Sars-cov-2 Rbd Antimentioning
confidence: 99%
“…To map antibody-escape mutations in a high-throughput manner, we leveraged a system for expressing conformationally-intact RBD on the surface of yeast cells ( Figure 1A). As described previously (Starr et al, 2020) , we created duplicate mutant libraries of the RBD from the Wuhan-Hu-1 strain of SARS-CoV-2 that together contained nearly all possible amino-acid mutations in the 201-residue RBD (they contain 3,804 of the 3,819 possible mutations, with >95% present as single mutants). Each yeast cell carries a short 16-nucleotide barcode that identifies the RBD mutant it expresses, enabling us to rapidly characterize the composition of the RBD mutant libraries via deep sequencing of the DNA barcodes.…”
Section: A Yeast-display System To Completely Map Sars-cov-2 Rbd Antimentioning
confidence: 99%
“…Identification of critical binding residues in this structure have provided valuable insights into viral recognition of the host receptor [24][25][26][27][28][29]. Deep mutagenesis studies have also revealed residues important for stability [30,31]. Compared with SARS-CoV, the SARS-CoV-2 S-protein has a 10-22-fold higher affinity for human ACE2 [24,25,32], due to more contacts in the interface that cover a larger surface area [29], and three mutational hotspots in the Sprotein that lead to a more specific and compact conformation [29,33].…”
Section: Introductionmentioning
confidence: 99%
“…We obtained datasets measuring replication fitness of all single-residue mutations to A/WSN/1933 (WSN33) HA H1 (Doud and Bloom, 2016), combinatorial mutations to antigenic site B in six HA H3 strains (Wu et al, 2020), or all single-residue mutations to BG505 and BF520 HIV Env (Haddox et al, 2018), as well as a dataset measuring the dissociation constant (Kd) between combinatorial mutations to SARS-CoV-2 Spike and human ACE2 (Starr et al, 2020), which we use to approximate the fitness of Spike.…”
Section: Resultsmentioning
confidence: 99%
“…• Fitness single-residue DMS of HA H1 WSN33 from Doud and Bloom 2016 • Fitness single-residue DMS of Env BF520 and BG505 from Haddox et al (Haddox et al, 2018) • ACE2 binding affinity combinatorial DMS of SARS-CoV-2 from Starr et al (Starr et al, 2020) • Escape single-residue DMS of HA H1 WSN33 from Doud et al 2018 for mutations to a viral sequence that preserve fitness while being antigenically different. This corresponds to a mutant sequence that is grammatical but has high semantic change with respect to the original (e.g., wildtype) sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation